Assessment Quality of Life in Children with Cerebral Palsy, Ages 2–18 Years - Alfira Nailatul Izzah; Irwanto Irwanto; Andriati Andriati; Prastiya Indra Gunawan (Universitas Airlangga, 2021)
Background: Cerebral palsy is non-progressive disorder that can cause limited movement and lead to postural deformity in children, which can affects all the psychosocial aspects and, thus, impacts children’s’ quality of life as well. Assessment of quality of life is important to evaluate suitable intervention measures for children with cerebral palsy. Purpose: This study aims to investigate the domains and determine the quality of life in children with cerebral palsy between ages 2 and 18. Methods: This was a descriptive study that employed a cross-sectional design approach. Primary data was obtained through a questionnaire. This study used the pediatric quality of life inventory (PedsQL)TM 3.0 cerebral palsy module. The study was conducted from November 2019 to February 2020. The data was collected at the Department of Medical Rehabilitation at the Dr. Soetomo Hospital, Peduli CP Foundation, and the Happy CP Community. This study involved 52 subjects, aged 2–18 years. Results: Almost all of the subjects (76.90%) had an impaired or poor quality of life. From the seven existing domains, only one domain received a good score: the domain of movement and balance. Conclusion: Based on the PedsQLTM 3.0 cerebral palsy module, parents reported that the quality of life in children (ages 2–18 years) having cerebral palsy was still low. Only the movement and balance domain got a good score.